Pelatihan Pemanfaatan Google Data Studio Untuk Visualisasi Data Bagi Para Guru SMKS Yapinuh Muara Gembong Kabupaten Bekasi Jawa Barat - Ali Idrus; Lipur Sugiyanta; Murien Nugraheni; Egan Alif Zanetti; Rosa Aulia Nisa; Syalva Syadila (Jurnal TUNAS, 2023)
This Community Service (PkM) was carried out at the Yapinuh Muara Gembong Private Vocational High School (SMKS) in the form of training for teachers and administrative staff on the use of google data studio to visualize data at SMKS Yapinuh online. Currently, the data in SMKS Yapinuh is still stored on computer devices owned by SMKS Yapinuh, but the data has not been able to provide information to school residents and the community directly. If school residents or the community want to get information related to data at SMKS Yapinuh, they must go through staff first because of their limited access rights. The existing data is also still in the form of raw data and the data display is less attractive. Therefore, a medium is needed that can overcome this. In this service, we will provide a solution by utilizing Google Data Studio to visualize data to make it more interesting so that it can be displayed on the SMKS Yapinuh website. The training method is carried out in a hybrid manner (online and offline) using Google Data Studio media as data visualization software. This Community Service Program (PkM) will focus on teachers and staff at SMKS Yapinuh. This PKM program will be guided directly by the service program proposal team. This PkM program aims to produce good quality information services by utilizing the application. So that SMK Yapinuh can be helped in the process of visualizing data and displaying it online.